PENGARUH PENERAPAN MODEL KOOPERATIF TWO STRAY TWO STAY TERHADAP HASIL BELAJAR PKN - Wayan Sinta Wati; Adelina Hasyim; Yunisca Nurmalisa (FKIP Unila, 2015)
The purpose of this research was to determine the influence of cooperative learning model two stray and two stay type toward civic education students learning result at first year of social studies 1. This research used quasi experiment. Object of research was the influence of cooperative learning model two stray and two stay type toward civic education students learning result at first year of social studies 1. Subjects of research were the first year of social studies students. The data analysis technique used quantitative-descriptive method. Result of the research showed that the influence of cooperative learning model two stray and two stay type toward civic education students learning result at first year of social studies 1 was higher than civic education students learning result at first year of social studies using conventional methodTujuan penelitian untuk mengetahui pengaruh model pembelajaran kooperatif tipe two stray two stay terhadap hasil belajar PKn siswa kelas X IPS 1. Penelitian menggunakan metode penelitian kuasi eksperimen. Objek penelitian adalah pengaruh penerapan model pembelajaran kooperatif tipe two stray two stay terhadap hasil belajar PKn siswa kelas X IPS 1 dan subjek penelitian adalah siswa kelas X IPS 1. Teknik analisis data dengan metode kuantitatif-deskriptif. Dari hasil penelitian dapat diketahui pengaruh model pembelajaran kooperatif tipe two stay two stray terhadap hasil belajar siswa kelas X IPS 1 lebih tinggi dari pada model pembelajaran konvensional.Kata kunci: pengaruh, kooperatif, two stray two stay.